Effect Of Interval Exercise Versus Continuous Exercise On Increases Energy Expenditure On A Treadmill - Waritsu, Cakra; Utomo, Dwikora Novembri; Sari, Gadis Meinar (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study is a pre-experiment with a posttest-only design research design using 16 obese women aged 19-23 years old, body mass index (BMI) 25-35 kg/m2, percentage body fat (PBF) above 30% and fasting blood glucose (FBG) below 100 mg/dL, normal hemoglobin (Hb), normal systolic and diastolic blood pressure, normal resting heart rate, VO2max25-30 mL/kg/min and randomly divided into two groups, namely IE (n=8, interval exercise) and CE (n=8, continuous exercise). Interval exercise and continuous exercise interventions were carried out at 08.00 a.m. for 40-45 minutes using a treadmill. The measurement of energy expenditure was using OMRON Caloriscan HJA-306-EW. Data analysis techniques used the Independent-Samples T Test with the Statistical Package for Social Science (SPSS). The results obtained mean energy expenditure on IE (251.750±19.775) kcal and CE (278.750±23.334) kcal (p=0.026). Based on the results of the study concluded that continuous exercise increases energy expenditure compared to interval exercise in obese women.